Poverty and Income Seasonality in Bangladesh - Khandker, Shahidur R. (2012)
Seasonal poverty in Bangladesh, locally known as monga, refers to seasonal deprivation of food during the pre-harvest season of Aman rice. An analysis of household income and expenditure survey data shows that average household income and consumption are much lower during monga season than in other seasons, and that seasonal income greatly influences seasonal consumption. However, lack of income and consumption smoothing is more acute in greater Rangpur, the North West region, than in other regions, causing widespread seasonal deprivation. The analysis shows that agricultural income diversification accompanied by better access to micro-credit, irrigation, education, electrification, social safety net programs, and dynamic labor markets has helped reduce seasonality in income and poverty in regions other than Rangpur in the recent past. Hence, government policies should promote income diversification through infrastructure investments and provide income transfers to the targeted poor to contain income seasonality and poverty in this impoverished part of Bangladesh.